Incidence And Patterns of Sexual Offenses Among Minors: An Analysis Under The POCSO Act 2012 At A Tertiary Centre - Bale, Priyanka; Sawardekar, S.G.; Rathod, G.D.; Dere, R.C. (Journal of Neonatal Surgery, 2025)
Sexual offenses against minors are a significant public health issue and the Protection of Children from Sexual Offenses (POCSO) Act, 2012 aims to combat these crimes. The study describes the demographic and clinical profiles of the minor victims of sexual offenses, thus illuminating patterns and contributing factors to abuse. This prospective observational study consisted of 176 minors less than 18 years of age, followed up over a period of two years from a tertiary care center in Mumbai. It showed that 84.1% were female victims and 57.4% fell within the 12-18-year age bracket. Most attacks took place in the daytime. In most cases, more than 24 hours passed before reporting the attacks. Victims often knew their assailants, and the non-consensual acts took place in 68.8% of cases. Genital injuries occurred in 20.5%, and penetration took place in 70.5%. The patterns of abuse differed according to gender and age, thus pointing out the importance of targeted intervention. Early intervention, legal aid, and counseling are essential factors for effective management.